The role of team communication, team leadership, and team time management on SAR team performance in Malaysia / Norsyazwani Ab Halim ...[et al.] - Ab Halim, Norsyazwani; Ahmad Zawawi, Azlyn; Ahmad Zawawi, Azita; Kamarunzaman, Nur Zafifa (Universiti Teknologi MARA, 2021)
Teamwork is a cooperative process that encourages personnel to achieve specific aims, whereby the members work together to achieve shared goals. The practice of teamwork is vital in any organization. One of many organizations that utilize teamwork is the Fire and Rescue Department of Malaysia (FRDM). FRDM'S most prominent activities involve Search and Rescue (SAR) teams. A SAR team refers to a group of individuals with the necessary skills and knowledge to find people in distress due to natural disasters or getting into difficulty in distress mountainous or desert regions. Several studies suggested that the SAR team's main issue is poor communication between the leader and members, leading to problems tracing accidents, team movements, and the incident location. There is still a lack of study focus on team performance, specifically in the SAR team context. Most of the previous scholars addressing team performance in military and business organizations. This study proposes to examine the relationship between team communication, team leadership, and team time management on the team performance of SAR teams. A total of 100 SAR team members from nine selected states in Peninsular Malaysia participated in this study. Data was collected using a set of questionnaires which were distributed to the SAR team of FRDM. The hypotheses were analyzed using Partial Least Squares (PLS) and the Statistical Package for the Social Sciences (SPSS). The results indicated a significant and positive relationship between communication, leadership, and time management towards team performance. This study would provide valuable inputs for the team, especially the search and rescue squad.